Low gas consumption in tracking detectors for outdoor applications. Issue 1 (1st November 2022) - Nyitrai, G; Hamar, G; Varga, D
Abstract : Gaseous detectors are one of the popular particle tracking technologies in high energy physics, and there are multiple applications where the detectors must tolerate outdoor conditions, e.g. in the emerging field of muography. Gaseous tracking detectors are attractive choices due to their high efficiency, good resolution and large sensitive area at a reasonable cost and low weight, but to achieve these, the gas system is usually not sealed. Continuous gas flow results gas consumption and thus regular gas cylinder replacement which limits applicability. In this paper we present a practical solution to reduce gas flow to a negligible level, keeping the construction cost-efficient and low weight, by a properly chosen buffer tube at the end of the gas line, which makes the system able to withstand large temperature and pressure fluctuations.